Amalan pendekatan inkuiri guru dalam pengajaran Sains sekolah menengah - Mohd. Zain, Muhammad (2013)
The aim of the study is to identify the level of inquiry approach practiced by science teachers of secondary school and their understanding about inquiry as well. In additional, the study also identify the constrains of inquiry approach in science teaching and learning. To achieved the stated purposes, a research using qualitative method had been done to 41 secondary school science teachers from Kulaijaya district, Johor. Research instrument used were open-ended questionnaire and semi-structured interview. Collected data from the study was analyzed using content analysis method. Research findings show science teachers understanding about inquiry approach is very weak. They also couldn’t afford to understand the definition, phases and importance of inquiry approach. Low level of teachers understanding about inquiry lead them to leave inquiry practice or implementing low level of inquiry (structured inquiry). Besides weak understanding about inquiry, teachers were also attracted to do traditional teaching practice because of certain constraint such as lack of time, students with low ability, students immaturity and priority to accomplish syllabus of the subject. Research findings give a picture that an effort to improvise science teacher proficiency about inquiry approach must be taken either in preservice or in service to ensure the continuity of meaningful science learning in our classroom.